Numerical study on magnetic sun pointing and attitude recovery for CubeSats - Hai-Hong Zhao; Feng Tan; Hong-Hao Yue (Prognostics and System Health Management Conference, 2017)
CubeSats may tumble after they are released from the launch vehicle, or initiated by other mechanism failures. As a result, the solar energy of CubeSats may be exhausted. Then the attitude determination and control systems (ADCS) of CubeSats enter into the abnormal state. It is of critical importance for CubeSats to get enough energy and attitude recovery. In the present study, a simple and novel control technique is proposed to achieve the attitude detumbling, sun pointing and attitude acquisition of the CubeSat. The sun pointing and attitude recovery magnetic controller is proposed by modifying the conventional B-dot law and the cross product law without gyros based on the satellite dynamics. The ADCS of the CubeSat utilizes fewer sensors and actuators considering the least power consumption. The sun pointing and attitude recovery system is established by magnetic torquers, three-axis magnetometers, and sun sensors without global field of view (FOV). The performance of the proposed controller is then demonstrated by numerical simulations at different initial conditions, external disturbances, constraints or limits of magnetic torques. The numerical simulation results indicate that the CubeSat points the normal of solar panels towards the sun to get enough energy and re-establishes earth pointing control to make itself back to its normal operations.